Monetary Policy and Trade: An Engine for Economic Growth - Samsul Arifin (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2023)
Amidst on the debate of the trade openness (TO) importance in influencing an economic growth (EG) and the central bank policy rate (CBPR), it is necessary to analyze the long-term relationship by using ARDL. This paper aims to analyze the CBPR and TO influence on EG in ASEAN -3. This study examines the EG model which focuses on the effect of CBPR and the ratio of exports in which plus imports divided by GDP as a measure of TO in ASEAN-3. The Data was collected from IFS for Indonesia, Philippines and Thailand for the period 2007q1-2022q2. The ARDL test method is used to determine the long-term relationship among the EG, TO and CBPR variables with different degrees of the integration. The FMOLS, DOLS, and CCR testing is for check robustness. The study show that CBPR has a positive effect on the EG in ASEAN-3, although it is only in Indonesia, and in Philippines which is statistically significant. The TO positive effect on the EG in Indonesia and in Thailand, but it is not significant and it has a TO statistically significant negative effect on EG in Philippines. The importance of this research given the recent interest in globalization activities, so the role of TO has become very important. A better TO understanding whether import dominance or vice versa helps in understanding the impact of globalization on the country economy. This finding emphasizes on the export importance over the imports in the economy. However, there is not an academic research looks at the long-term relationship between monetary policy and trade openness on the economic growth with the various econometric models.